Iron, folic acid, and multiple micronutrient supplementation strategies during pregnancy and adverse birth outcomes in Botswana. Issue 6 (June 2022) - Caniglia, Ellen C; Zash, Rebecca; Swanson, Sonja A; Smith, Emily; Sudfeld, Christopher; Finkelstein, Julia L; Diseko, Modiegi; Mayondi, Gloria; Mmalane, Mompati; Makhema, Joseph; Fawzi, Wafaie; Lockman, Shahin; et al.
Summary: Background: Antenatal multiple micronutrient supplementation (MMS) with iron, folic acid, and other micronutrients might improve birth outcomes, but it is not currently universally recommended by WHO. Methods: In this observational cohort study, we surveyed pregnancies for adverse birth outcomes at eight hospitals from July, 2014, to July, 2018, and 18 hospitals from August, 2018, to December, 2020, in Botswana to assess four routine supplementation strategies in women presenting before 24 weeks' gestation: folic acid only, iron only, iron and folic acid supplementation (IFAS), and MMS. Women with singleton pregnancies; a known HIV status, age, and delivery site; haemoglobin measured within 7 days of presenting to antenatal care; and weight measured within 31 days of presenting to care were included in our analysis. Data were abstracted from the maternity obstetric record (a record of antenatal care) at the time of birth from all women giving birth at selected hospitals throughout the country. We estimated risk differences overall and in key subgroups, adjusting for demographic and clinical factors. Findings: Between July 6, 2014, and Dec 8, 2020, 96 341 eligible women (21 659 [22·5%] of whom had HIV) were included in the study. 36 334 (37·7%) women initiated iron only supplementation, 1133 (11·8%) initiated folic acid only supplementation, 23 101 (24·0%) initiated IFAS, and 31 588 (32·8%) women initiated MMS. Women who initiated iron only and folic acid only supplementation had higher risks of stillbirth, preterm birth, very preterm birth, low and very low birthweight, and neonatal death compared with women who received IFAS (adjusted risk differences for iron only supplementation vs IFAS ranged from 0·22% [95% CI 0·04 to 0·40] for neonatal death to 2·39% [1·78 to 3·00] for preterm birth; and adjusted risk differences for folic acid only supplementation vs IFAS ranged from 0·77% [–0·80 to 2·34] for neonatal death to 5·75% [1·38 to 10·13] for preterm birth), with greater difference in women with HIV and those aged 35 years and older. Compared with IFAS, women who initiated MMS had lower risks of preterm and very preterm births, and low and very low birthweight (adjusted risk differences ranged from –0·50% [–0·77 to 0·23] for very preterm birth to –1·06% [–1·69 to –0·42] for preterm birth). Interpretation: Nationwide data from Botswana support improved birth outcomes with MMS compared with IFAS. Funding: National Institutes of Health, National Institute of Child Health and Human Development, and National Institute of Allergy and Infectious Diseases.